The Effect of Health Care With Attitudes and Behavioral Control on Consumers' Buying Interest in Healthy Food Products - Ninda Ariyanti Setia Ningrum (Institute of Computer Science (IOCS), 2022)
Health concerns are increasing along with the development of healthy food products in the community. This study aims to analyze the influence of health care attitudes and behavioral controls on consumers' buying interests in healthy food products. Conduct quantitative research with a statistical analysis approach. The population in this study is consumers in the student category who have made product/goods transactions through Shopee throughout Indonesia. The study sample of 300 people was determined using purposive sampling. Data was collected using questionnaires that passed validity and reliability tests, and data were analyzed using AMOS with a 95 percent confidence level (p<0.05). The results showed that concern for health affects attitudes towards healthy food products (p = 0.000), health concern has a significant effect on subjective norms towards healthy food products (p = 0.000), and health concern has a significant effect on behavioral control felt in healthy food products (p = 0.000), attitudes towards healthy food products have a significant effect on buying interest in healthy food products (p = 0.004), subjective consumer norms have a significant effect on buying interest in healthy food products (p = 0.003), and perceived behavioral control has a positive and significant effect on buying interest in healthy food products (p = 0.000). Furthermore, consumers' interests in buying healthy food products have a positive and significant effect on health care through their attitudes and behaviors.